INNV-17. RESPONSE TO AVAPRITINIB IN A PEDIATRIC SPINAL CORD H3K27M-MUTANT GLIOMA PATIENT. (12th November 2021) - Mayr, Lisa; Madlener, Sibylle; Verena, Rosenmayr; Schmook, Maria; Stepien, Natalia; Baumgartner, Alicia-Christina; Dorfer, Christian; Haberler, Christine; Müllauer, Leonhard; Dieckmann, Karin; Peyrl, Andreas; Kim, Sean; et al.
Abstract: H3K27M-mutated diffuse midline glioma (H3K27M-DMG) may arise in the pons, thalamus and spinal cord generally having a dismal prognosis. Notably, H3K27M-DMG are driven by oligodendrocyte precursor-like cells which are partly sustained by PDGFRA signaling. Co-mutations including TP53, ACVR1, PDGFRA, KIT and PI3K pathway alterations are present in a subset of cases, and molecular profiling may allow detection of additional targetable alterations. However, small-molecule inhibitors often have limited efficacy associated with low blood-brain-barrier (BBB) penetration. Here, we report on a patient with spinal, leptomeningeal disseminated H3K27M-DMG treated with avapritinib, an orally administered, BBB-penetrant and highly selective KIT and PDGFR inhibitor, provided through a compassionate-use program. Initial therapy consisted of subtotal resection, focal radiotherapy and temozolomide (TMZ) resulting in disease stabilization. Ten months after diagnosis, leptomeningeal metastases were detected, biopsied and treated with local irradiation and TMZ. The patient subsequently received systemic and intrathecal chemotherapy augmented with dasatinib. Molecular analyses of the biopsy revealed the H3F3A and TP53 mutations present in the primary tumor, as well as de novo PDGFRA and KIT amplifications with gene copy numbers of 25 and 21, respectively. Upon further disease progression, therapy with avapritinib was initiated. Assessment of treatment response according to RANO criteria after four months revealed stable disease of the target lesion in the cerebellum and partial response of all non-target lesions. Avapritinib was generally well tolerated with lower limb edema (Grade 2), small intratumoral bleeding (Grade 1) and unrelated hydrocephalus (Grade 3) as reported adverse events. As precaution, treatment was interrupted and re-initiated after one week as the bleeding was stable. A ventriculoperitoneal shunt was implanted resolving the hydrocephalus. Pharmacokinetic analyses revealed up to 65% avapritinib plasma exposure and clinically relevant levels in cerebrospinal fluid. In summary, we report on first effective therapy of treatment-resistant H3K27M-DMG with avapritinib as clinical proof of concept.